PENINGKATAN PRESTASI BELAJAR IPS MATERI LINGKUNGAN ALAM DAN BUATAN MELALUI MEDIA TIGA DIMENSI - Handayani, Sri Rida (Jurnal Pendidikan Guru, 2018)
This research is an effort in improving the achievement of third grade students of SD Negeri 18 Pekanbaru on the subjects of Social Science and Natural Environment IPS through three dimensional media. The subjects in this study were all students of class III SD Negeri 18 Pekanbaru which amounted to 28 students, consisting of 15 male students and 13 female students. This research applied three dimensional media at the time of IPS learning. The findings of this study indicate that through three-dimensional media can improve learning achievement IPS class III SD Negeri 18 Pekanbaru. Can be seen from the results of the discussion that is on the cycle to cycle I, the number of increasing number of students who reached KKM increased as many as 6 students or 21%. From cycle I to cycle II the number of students increasing KKM increased by 8 students or 29%. From cycle II to cycle III the number of students increasing reaching KKM increased by 6 students or 21%. The data show that there is an increase in learning achievement from cycle I, cycle II, and cycle III that is upgrading 20 students or 71.4%.